Social Media Use By Ontario University Libraries: Challenges and Ethical Considerations - Collins, Gary; Quan-Haase, Anabel (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The application of social media by academic libraries is re-shaping traditional ideas of library services. The use of social media in Ontario’s university libraries demonstrates the divergent modes by which information technologies are utilized, as well as the challenges facing libraries in both adopting and using these tools. L’application des médias sociaux par les bibliothèques universitaires transforme les idées traditionnelles des services en bibliothèque. L’utilisation des médias sociaux dans les bibliothèques universitaires de l’Ontario démontre des modes divergents d’utilisation des technologies de l’information, ainsi que les défis auxquels font faces les bibliothécaires en termes d’adoption et d’utilisation de ces outils.